2017
DOI: 10.28933/ijnr-2017-042201
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate ameliorates memory deficits in mice exposed to passive avoidance paradigm

Abstract: Passive avoidance task is a rodent model of memory in which the animal learns to avoid an aversive stimulus precipitated by fear and it is always accompanied by inhibition of motor behavior. We have shown in our previous studies that methyl jasmonate (MJ), a bioactive compound isolated from Jasminum grandiflorum demonstrated memory enhancing effect in hippocampal-dependent memory tasks such as Y-maze and object recognition tests in mice. This present study was designed to investigate if MJ could ameliorate mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The studies revealed that significant memory enhancement in MeJA treated animals was observed as compared to LPS treated. The underlying mechanism has been linked to MeJA antioxidant, anti-inflammatory potential using In-vivo as well as In-Vitro screening models [46][47][48].…”
Section: Inhibition Of Neuronal Peroxidation and Oxidative Stressmentioning
confidence: 99%
“…The studies revealed that significant memory enhancement in MeJA treated animals was observed as compared to LPS treated. The underlying mechanism has been linked to MeJA antioxidant, anti-inflammatory potential using In-vivo as well as In-Vitro screening models [46][47][48].…”
Section: Inhibition Of Neuronal Peroxidation and Oxidative Stressmentioning
confidence: 99%